ANALYSIS OF POST-MODIFIERS NOUN PHRASE ON SUBJECT SENTENCES IN THE ABSTRACT OF THESIS OF ENGLISH STUDY PROGRAM STUDENTS 2024 - Sihombing, Santa Regina; Sitepu, Dhea Natasya; Situmeang, Sonya Lauri; Sembiring, Yena Jorena; Munthe, Melda Veby Ristella (JURNAL RECTUM: Tinjauan Yuridis Penanganan Tindak Pidana, 2024)
This research is entitled “Analisis Post-Modifiers Noun Phrase pada Subjek Kalimat dalam Abstrak Skripsi Mahasiswa Program Studi Bahasa ingris ”. The purpose of the research is to explain the type and the constituents of post-modifier contained in the subject of the sentence on the abstract of English education Department students' juournal in 2023-2024. To find the answer of this problem, the method applied is qualitative – descriptive with syntactic approach. The theories applied are from Vespoor and Sauter, Aarts, Meyer, and Tallerman. This research explains about two types of post-modifier contained in subject of the sentence on the abstract. First, there are 25 post-modifiers found in prepositional phrase marked with ‘of’ and ‘for’ after the head. Second, there are two post-modifiers found in adjective phrase marked with words explaining the head. Based on the analysis of 22 abstracts, the writer found 11 different patterns of post-modifier in prepositional phrase and two different patterns of post-modifier in adjective phrase